Borane-bridged ruthenium complex bearing a PNP Ligand: synthesis and structural characterization - Xu, Yijing; Rettenmeier, Christoph Alexander; Plundrich, Gudrun; Wadepohl, Hubert; Enders, Markus; Gade, Lutz H. (Organometallics, 2015)
Reaction of the precursor complex [RuHCl(CO)(PPh3)3] with the PNP protioligand CbzdiphosH in toluene resulted in the formation of two stereoisomeric hydrido complexes, [(CbzdiphosH)RuHCl(CO)] (A). The addition of a strong base (KOtBu or LiEt3BH), on the other hand, led to the formation of the 1,2-dehydrochlorination product [(Cbzdiphos)RuH(CO)]. The reaction of the latter with BH3·THF at room temperature led to the 1,2-addition of the BH3 moiety to the Ru-N function, forming a RuNBH cycle in [(CbzdiphosHBH2)RuH(CO)] (B). The same borane-bridged compound was obtained when complex A was treated with NaBH4 in THF. The BH2 group forms a bridging unit between the carbazole-N atom and one of the ruthenium-bound hydrides.
Gesehen am 9.08.2020